Rhizosphere soil bacterial communities and nitrogen cycling affected by deciduous and evergreen tree species. Issue 7 (13th July 2022) - Liu, Jiantong; Wang, Xinyu; Liu, Lin; Wu, Xuefeng; Xia, Zhichao; Guo, Qingxue
Abstract: Deciduous and evergreen trees differ in their responses to drought and nitrogen (N) demand. Whether or not these functional types affect the role of the bacterial community in the N cycle during drought remains uncertain. Two deciduous tree species ( Alnus cremastogyne, an N2 ‐fixing species, and Liquidambar formosana ) and two evergreen trees ( Cunninghamia lanceolata and Pinus massoniana ) were used to assess factors in controlling rhizosphere soil bacterial community and N cycling functions. Photosynthetic rates and biomass production of plants, 16S rRNA sequencing and N‐cycling‐related genes of rhizosphere soil were measured. The relative abundance of the phyla Actinobacteria and Firmicutes was higher, and that of Proteobacteria, Acidobacteria, and Gemmatimondaetes was lower in rhizosphere soil of deciduous trees than that of evergreen. Beta‐diversity of bacterial community also significantly differed between the two types of trees. Deciduous trees showed significantly higher net photosynthetic rates and biomass production than evergreen species both at well water condition and short‐term drought. Root biomass was the most important factor in driving soil bacterial community and N‐cycling functions than total biomass and aboveground biomass. Furthermore, 44 bacteria genera with a decreasing response and 46 taxa showed an increased response along the root biomass gradient. Regarding N‐cycle‐related functional genes, copy numbers of ammonia‐oxidizing bacteria (AOB) and autotrophic ammonia‐oxidizing archaea (AOA), N2 fixation gene ( nifH ), and denitrification genes ( nirK, nirS ) were significantly higher in the soil of deciduous trees than in that of the evergreen. Structural equation models explained 50.2%, 47.6%, 48.6%, 49.4%, and 37.3% of the variability in copy numbers of nifH, AOB, AOA, nirK, and nirS, respectively, and revealed that root biomass had significant positive effects on copy numbers of all N‐cycle functional genes. In conclusion, root biomass played key roles in affecting bacterial community structure and soil N cycling. Our findings have important implications for our understanding of plants control over bacterial community and N‐cycling function in artificial forest ecosystems. Abstract : Short‐time drought had less effect on bacterial communities than plant life habit. Root biomass is the main factor driving changes in soil bacterial communities. Highly diverse forests have high N cycling rates and stable bacterial communities. Bacterial taxa show different response along root biomass gradient.